Transnational Motherhood: Health of Hispanic Mothers in the United States Who Are Separated From Children - McCabe, Brian E. (J Transcult Nurs, 2016)
Immigration often results in the separation of families, and in particular transnational parenting, which is the separation of mothers from children. Transnational mothers may have greater risks for poor mental health and behavioral conditions such as substance abuse, violence, sexual risk, and depression. This study was a secondary analysis of self-reported data from 425 Hispanic mothers (328 with no separations, 60 separated from an adult child, and 37 separated from a minor child) enrolled in a randomized trial of a sexual health group intervention in South Florida (USA). Separations were related to mother’s age, years in the United States, family income, number of people living on income, acculturation to the United States, occupational/economic stress, immigration stress, and lifetime exposure to abuse. A follow-up analysis described the types of childhood or adulthood abuse experienced by mothers with separations. These findings provide new information for nurses about the experience of immigrant mothers.